Discussion on Russian Émigré Literature in the “Mech” Journal and Around It - Anna V. Protopopova; Ivan A. Protopopov (Studia Litterarum)
The understanding of the ways of development of Russian emigrant literature was reflected in the discussion between V.G. Fyodorov, D.V. Filosofov and D.S. Merezhkovsky in the Warsaw journal "Mech" ("Sword") and further in the polemic between V.F. Khodasevich and G.V. Adamovich. Should national literature in emigration be connected both with the native language and with national traditions and culture, or should it be based on the Western cultural tradition? For Khodasevich, the possibility of the development of literature was connected with the creation of new poetic artistic forms based on the national tradition, while Adamovich believed that it needed an artistic expression that was a documentary record of life, which was linked to an orientation towards Western European literary models.